The moderating role of socio-economic status in digital marketing adoption and agribusiness sustainability among rural youth - Nor Afifah Yusof; Mohd Noor Hidayat Jimainal; Rudy Ansar; Brahim Chekima; Ng, Yen Phin; Shalahuddin Shalahuddin (RSIS International, 2025)
This conceptual paper examines the socioeconomic status (SES) moderates the use of digital marketing tools in sustainable agribusiness among rural youths. By using an integrated framework based on the Technology Acceptance Model (TAM) and the Innovation Diffusion Theory (IDT), the study examines key factors influencing digital marketing adoption. The three constructs which have been included in this study are perceived usefulness (PU), perceived ease of use (PEOU), and social influence. TAM has focused on perceived characteristics in the adoption of technologies, while the IDT model has favoured the influence of the social context and community. The combination of these models is significant in offering an overall framework for understanding the individual, social and contextual antecedents of the adoption decision-making process. This paper contributes to the literature by arguing that SES plays a critical role in the moderation of the relationship between PU, PEOU, social influence, and agribusiness sustainability. The insights presented in the paper offer a valuable recommendation for policymakers, academics and other related stakeholders in addressing SES disparities among rural youths and promoting inclusive digital adoption in agribusiness.